An Essay on Attributes of Leadership - Mohd Ossama (International Journal of Engineering and Management Research, 2020)
Leadership is essential at all levels and all major organizations; it gives direction and perspective and sustained vision, which is translated into reality. Leadership encompasses all positions and covers many areas such as business, governmental, political and social. We look at some of the attributes of leadership in this essay.